The Effect of EdrawMind-Based Mind Mapping Learning Media and Learning Motivation on History Learning Outcomes at SMA Negeri 70 Jakarta - Raka Rahman Putra; M. Fakhruddin; Abrar Abrar (Universitas Hamzanwadi, 2026)
This study examines the effectiveness of EdrawMind mind mapping media on motivation and learning outcomes in History, specifically on the topic of the Indonesian people's resistance to colonialism at SMA Negeri 70 Jakarta. The research aims to analyze the influence of EdrawMind on learning outcomes, test the relationship between motivation and learning outcomes, and identify its impact on student motivation. This quasi-experimental study with a nonequivalent control group design involved 72 grade XI students (36 experimental, 36 control) in the odd semester of the 2025/2026 academic year. Data were collected through questionnaires, tests, and observations, then analyzed using SPSS with T-tests, linear regression, and prerequisite tests. The results show: (1) EdrawMind did not have a significant effect on learning outcomes (p=0.944); (2) Motivation had a positive and significant effect on learning outcomes (p=0.006) with a contribution of 10.5%; (3) EdrawMind significantly increased learning motivation (p=0.000) with an average increase of 10.72 points. It is concluded that EdrawMind is effective in increasing motivation but has not yet impacted cognitive history learning outcomes.